Chapter 27: Velvet triangles and more: alliances of supranational EU gender equality actors - Ahrens, Petra (Edward Elgar Publishing, 2023)
Building feminist alliances has always been an important feature of supranational European Union (EU) gender equality policy and politics. Historically, a so-called 'velvet triangle' consisting of feminist actors inside and outside of EU institutions committed to promoting gender equality has been the most tangible and best-researched network. Overall, feminist and women's movements have played a major role in shaping the relationships between EU institutions and civil society and equally the content of EU gender equality politics and policies. The chapter provides an overview of: first, the history and formal rules of EU-civil society relationships; second, crucial changes to supranational alliances in gender equality; and third, current challenges to gender equality alliances in EU governance.